2014
DOI: 10.5194/bg-11-3015-2014
|View full text |Cite
|
Sign up to set email alerts
|

Using biogeochemical data assimilation to assess the relative skill of multiple ecosystem models in the Mid-Atlantic Bight: effects of increasing the complexity of the planktonic food web

Abstract: Abstract. Now that regional circulation patterns can be reasonably well reproduced by ocean circulation models, significant effort is being directed toward incorporating complex food webs into these models, many of which now routinely include multiple phytoplankton (P) and zooplankton (Z) compartments. This study quantitatively assesses how the number of phytoplankton and zooplankton compartments affects the ability of a lower-trophic-level ecosystem model to reproduce and predict observed patterns in surface … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 40 publications
1
49
0
Order By: Relevance
“…Xiao and Friedrichs (2014b), for example, found that while the optimization of a range of NPZD models to satellite data tended to reduce model-data misfit, this was often achieved through the adoption of extremely unrealistic parameter estimates, sometimes being multiple orders of magnitude higher or lower than their best a priori estimates. The same authors (Xiao and Friedrichs, 2014a) showed that adding synthetic noise to assimilated satellite data led to the introduction of similar errors, and a significant deterioration of one model's predictive skill. The extreme parameter estimates were not representative for the system and the model performance turned out to be poor when the model was tested against independent data that were not used during the optimization procedure.…”
Section: Cross-validationmentioning
confidence: 99%
See 4 more Smart Citations
“…Xiao and Friedrichs (2014b), for example, found that while the optimization of a range of NPZD models to satellite data tended to reduce model-data misfit, this was often achieved through the adoption of extremely unrealistic parameter estimates, sometimes being multiple orders of magnitude higher or lower than their best a priori estimates. The same authors (Xiao and Friedrichs, 2014a) showed that adding synthetic noise to assimilated satellite data led to the introduction of similar errors, and a significant deterioration of one model's predictive skill. The extreme parameter estimates were not representative for the system and the model performance turned out to be poor when the model was tested against independent data that were not used during the optimization procedure.…”
Section: Cross-validationmentioning
confidence: 99%
“…Adjoint versions of plankton ecosystem models have been constructed primarily to compute ∇J for an efficient search with gradient descent algorithms in the parameter-cost function manifold (e.g. Lawson et al, 1996;Fennel et al, 2001;Schartau et al, 2001;Spitz et al, 2001;Friedrichs, 2002;Faugeras et al, 2003;Zhao et al, 2005;Friedrichs et al, 2007;Xiao and Friedrichs, 2014a). To elucidate the nature of adjoint model developments is beyond the scope of this paper, but a brief summary about adjoint model developments is given in the Appendix C. The advantage is that all elements of the Hessian can be approximated with finite differences of adjoint model results (e.g.…”
Section: The Hessian: Its Approximation and Inversionmentioning
confidence: 99%
See 3 more Smart Citations